2012
DOI: 10.6061/clinics/2012(12)10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brazilian Cardioprotective Diet Program on risk factors in patients with coronary heart disease: a Brazilian Cardioprotective Diet randomized pilot trial

Abstract: OBJECTIVE:To evaluate the effectiveness of the Brazilian Cardioprotective Diet Program in reducing blood pressures, fasting glucose levels and body mass indices in patients with established atherothrombotic disease.METHOD:This randomized controlled pilot trial included outpatients who were over 45 years of age with atherothrombotic cardiovascular disease. Group A, who received the Brazilian Cardioprotective Diet Program, had weekly sessions with dietitians. Groups B and C received the usual dietary therapy tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
1
23
0
4
Order By: Relevance
“…Also in Brazil, Marchioni et al 55 examined data from the 2002-03 family budget survey and identified two patterns, a "dual pattern" -which comprised foods recognised as being beneficial to health, such as fruit, vegetables and yoghurt, but also contained a contribution from foods with adverse health effects, such as sweets and desserts, processed meats, ready meals -and, on the other hand, a "traditional pattern" comprising foods normally used in home preparations, such as rice, beans, eggs, roots and tubers. In their results, they highlighted the existence of a dual type of food pattern, i.e., of healthy and unhealthy foods, very like consumption patterns already observed in other studies and associated with higher risk of CVDs 54 .…”
Section: Other Means Of Defining Food Patternssupporting
confidence: 66%
See 1 more Smart Citation
“…Also in Brazil, Marchioni et al 55 examined data from the 2002-03 family budget survey and identified two patterns, a "dual pattern" -which comprised foods recognised as being beneficial to health, such as fruit, vegetables and yoghurt, but also contained a contribution from foods with adverse health effects, such as sweets and desserts, processed meats, ready meals -and, on the other hand, a "traditional pattern" comprising foods normally used in home preparations, such as rice, beans, eggs, roots and tubers. In their results, they highlighted the existence of a dual type of food pattern, i.e., of healthy and unhealthy foods, very like consumption patterns already observed in other studies and associated with higher risk of CVDs 54 .…”
Section: Other Means Of Defining Food Patternssupporting
confidence: 66%
“…In 2012, Weber et al 54 published the findings of a pilot study of a cardio-protective Brazilian diet (DICA-Br) conducted at the Hospital do Coração (HCOR) in São Paulo for application in a multicentre study. One of the purposes of the study was to adapt the Mediterranean diet to a Brazilian pattern, while encouraging consumption of regional foods accessible to a large part of Brazil's population.…”
Section: Other Means Of Defining Food Patternsmentioning
confidence: 99%
“…9,11 With respect to the sleep pattern, it is altered, as a possible consequence, that 46% of respondent's report stress. It is known that sleep disorders can trigger a series of changes at the individual, since behavioral changes such as tiredness and irritability and can even contribute at the same time the other factors, with the emergence of CVD.…”
Section: Discussion Of the Datamentioning
confidence: 99%
“…The intervention has the main purpose of developing a Brazilian cardioprotective diet that achieves standard nutritional recommendations for treatment of CVD and, concurrently, incorporates local food products to respect regional habits, multi-cultural factors and affordability. The main results of the BALANCE Program were previously published (19)(20)(21) showing diet quality improvement after a 48-months follow-up, but no differences in mortality or cardiovascular events.…”
Section: Introductionmentioning
confidence: 95%